Prototype of Warehouse Automation System Using Arduino Mega 2560 Microcontroller Based on Internet of Things - Yusuf Kurnia; Jeksen Li Sie (bit-Tech, 2019)
This research aims to collaborate between automation systems involving 3 main components namely Actuators, transducers / sensors, and microcontrollers are also implementations of IoT that are implemented in accessing, controlling, supervising, and monitoring all activities that are generally related to warehousing as well as increasing the efficiency and security of those who do not have the authority to access the room. In This research the hardware used as a control system is an integrated circuit board ARDUINO MEGA 2560 based on ATMega2560 Chipset that has 13 I / O pins for analog pins and 40 digital pins, the selection of that number of I / O pins as anticipated if this design will be developed further by using instruments that require hardware to support operational activities in specific warehouses of general, ESP8266 as a module device used for IoT communication using the Blynk application on Smartphone devices, and the RFID Mifare RC522 module used to access the room if there is an internet connection failure